Collective Cyberbullying Ditinjau dari Psikologi Sosial - Yasmin Sahnaz Almuntaha; Ikhwanul Ihsan Armalid (Universitas Negeri Malang, 2023)
With the development of communication technology, the use of social media in Indonesia is also increasing. The high use of social media has led to an increase in various criminal behaviors, such as cyberbullying. Cyberbullying is the act of insulting or hurting others through social media. This widespread social media influence can turn the influence of behavioral transmission on other users into collective behavior (collective cyberbullying). This case has had a very negative impact on aspects of the victim’s life. Therefore, literature review research is carried out in order to know the specific factors and impact of collective cyberbullying from the perspective of social psychology. The results of this study show that there are several key factors, including technological development, individual psychology, community understanding, and social and environmental influences. This form of cyberbullying behavior can also be explained based on the transmission theory of Gustav Le Bon, where there are three mechanisms that influence the formation of collective behavior: anonymity, transmission, and ease of being influenced. The impact on victims was then categorized into four categories: psychological, psychosocial, academic, and physical.Abstrak Seiring berkembangnya teknologi komunikasi semakin tingginya juga penggunaan media sosial di masyarakat Indonesia. Tingginya penggunaan media sosial mengakibatkan meningkatnya berbagai perilaku kejahatan seperti cyberbullying. Cyberbullying merupakan perilaku menghina atau menyakiti orang lain melalui media sosial. Pengaruh media sosial yang luas ini dapat menimbulkan pengaruh penularan perilaku pada pengguna lain menjadi sebuah perilaku kolektif (collective cyberbullying). Kasus ini membawa dampak buruk yang sangat berpengaruh pada aspek kehidupan korban. Oleh karena itu, penelitian literature review dilakukan agar dapat mengetahui faktor dan dampak spesifik pada collective cyberbullying yang ditinjau dari perspektif Psikologi Sosial. Hasil penelitian ini menunjukkan bahwa terdapat beberapa faktor utama antara lain perkembangan teknologi, psikologis individu, pemahaman masyarakat, dan pengaruh lingkungan sosial. Bentuk perilaku cyberbullying ini juga dapat dijelaskan berdasarkan Teori Penularan milik Gustav Le Bon, dimana terdapat tiga mekanisme yang mempengaruhi pembentukkan perilaku kolektif, yaitu anonimitas, penularan, dan kemudahan untuk dipengaruhi. Kemudian dampak pada korban dikategorikan menjadi empat kategori, yakni dampak psikologis, psikososial, akademik, dan fisik.